Danian (Early Paleocene) echinoids from the Roca Formation, northern Patagonia, Argentina - Martínez, Sergio (2011)
Stratigraphically well-constrained echinoids from the Roca Formation in the province of Rio Negro (Patagonia, Argentina) are analysed in detail. The poorly known Linthia? joannisboehmi OPPENHEIM in BÖHM, 1903, recently reassigned to Paraster, is demonstrated to comprise in fact two distinct species, Linthia? joannisboehmi and Linthia parmae n. sp. In addition, specifically indeterminate species of Plesiaster and Hemiaster and a basal holasteroid are recorded. The analyses of calcareous nannofossil assemblages of the echinoid-bearing strata document their early Paleocene (Danian) age, which has an impact on patterns of survivorship across the K/Pg boundary.